Gene and antibody molecule - Sofia Mubarika Haryana, Sofia Mubarika Haryana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
Five major structural types of immunoglobulin in man can be distinguished. i. e. immunoglobulin G (abbreviated to IgG), IgM, IgA, IgD and IgE. Each type of immunoglobulin can synthesize specific antibody according to the inducing antigen. The specificity of immunoglobulin molecule is found in the antigen-binding fragment.Actually the specificity and the diversity of the immunoglobulin is controlled by the gene in the chromosome. The diversity and where the assembly of immunoglobulins is held are described.Key Words: immunoglobulin - antigen-binding fragment - central dogma - protein synthesis - germ line theory